Environmental Character: Environmental Feelings, Sentiments and Virtues - Frasz, Geoffrey (ETHICS IN PROGRESS, 2016)
An argument is made that to further develop the field of environmental virtue ethics it must be connected with an account of environmental sentiments. Openness as both an environmental sentiment and virtue is presented. This sentiment is shown to be reflected in the work of Barbara McClintock. As a virtue it is shown to a mean between arrogance and the disvaluing of individuals, a disposition to be open to the natural world and the values found there. Further development of EVE is then shown to require a connection with an account of environmental wisdom.